Electronic ceramics based on polycrystalline SnO2, TiO2 and (Sn xTi1-x)O2 solid solution - Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP] (ABM, ABC, ABPol, 2006)
In the present text we discuss on electronic properties arising from polycrystalline semiconductor ceramics of SnO2, TiO2 and (Sn xTi1-x)O2 solid solution rutile-type structure. This is intended to be a short overview of the most recent papers in this area. One of the most important content discussed in this text is based on sinterability of these polycrystalline ceramics, which depends on the target application used to project porous or highly dense microstructure. The majority of discussion is focused in two main applications: varistor and sensor. In both applications there are similarities involved in the control of the sensor and varistor properties, which can mainly ascribed to the grain boundary structure and composition. The similarities found are consistently explained by the fact that all of these n-type semicondutor ceramics have the tendency to establish a grain boundary region with a p-type semiconductor nature (due to metal transition atoms segregated at the grain boundary region and then favors negative charged species to adsorb and enrich this region). This configuration enables electrons to become localized on the surfaces, giving rise to a negative surface and, as a result, electron depletion layers are formed, acting as potential barriers which control the properties of the mentioned devices.
Keywords: varistor; sensor; polycrystalline system; tin dioxide; titanium dioxide